Gastrointestinal fistulae: conservative vs surgical management - Shaikh, Aftab H.; Dhanorkar, Tanay S.; Bhandarwar, Ajay H.; Chavhan, Shivali; Shrotri, Gautam (International Surgery Journal, 2024)
Background: Gastrointestinal fistulae are abnormal connections between two hollow organs of the gastrointestinal tract or between the hollow organ and the skin. They remain a major clinical problem, especially if complicated by sepsis, bacteraemia or cancer. General Principles of fistula management consist of- Phase of Diagnosis, Stabilization and Management. Methods: The study was conducted in Sir JJ Group of Hospitals, Mumbai. A total of 34 patients with gastrointestinal fistulae were studied between January 2020 to January 2023. The patients were studied on the basis of presenting signs and symptoms, details of initial surgery performed, investigations pertaining to the condition and their management. Results: Out of the 34 cases, 44% of the cases were from the small intestine, 39% cases we]re from the large intestine, and the rest of the cases were from stomach, duodenum, gastrojejunostomy site and appendicular stump following appendicectomy. Conclusions: The database of our retrospective study regarding age and sex incidence, clinicopathological features and therapeutic outcome was comparable to other studies in various literatures.